Balloon aortic valvuloplasty: current status and future prospects. (4th May 2022) - Dall'Ara, Gianni; Grotti, Simone; Guerrieri, Giuseppe; Compagnone, Miriam; Spartà, Daniela; Galvani, Marcello; Tarantino, Fabio
ABSTRACT: Introduction: Balloon aortic valvuloplasty (BAV) improves hemodynamic and clinical status of patients with severe aortic stenosis (AS) for a limited period of 6–12 months. However, there is a high number of procedures performed worldwide and an upward trend over the last decades. Areas covered: Epidemiology of AS and the advent of transcatheter aortic valve implantation (TAVI) contribute to the extensive referral of patients. The expansion of recommendations for TAVI has occasionally led to financial reimbursement-related problems that do not exist for BAV. BAV is indicated as a bridge to valve replacement, to decision in complex cases, and to extracardiac surgery. BAV may play a role in preparing for TAVI and optimizing procedural results. The minimalist approach and reduced complication rate make it applicable in fragile patients. Expert opinion: In the near future, BAV will continue to be a useful asset in managing patients with AS given the multiple indications, broad applicability, safety profile, low cost, and repeatability. Specific studies are necessary to explore technical solutions, stronger indications, the finest technique, and to standardize the procedural result. Pending the development of potential competitive devices, the role that BAV plays will remain closely intertwined with the one played by TAVI.